Analytical and Clinical Assessment of a Portable, Isothermal Recombinase Polymerase Amplification (RPA) Assay for the Molecular Diagnosis of Urogenital Schistosomiasis - Archer, John (Molecules, 2020)
Accurate diagnosis of urogenital schistosomiasis is crucial for disease surveillance and control. Routine diagnostic methods, however, lack sensitivity when assessing patients with low levels of infection still able to maintain pathogen transmission. Therefore, there is a need for highly sensitive diagnostic tools that can be used at the point-of-care in endemic areas. Recombinase polymerase amplification (RPA) is a rapid and sensitive diagnostic tool that has been used to diagnose several pathogens at the point-of-care. Here, the analytical performance of a previously developed RPA assay (RT-ShDra1-RPA) targeting the Schistosoma haematobium Dra1 genomic region was assessed using commercially synthesised S. haematobium Dra1 copies and laboratory-prepared samples spiked with S. haematobium eggs. Clinical performance was also assessed by comparing diagnostic outcomes with that of a reference diagnostic standard, urine-egg microscopy. The RT-ShDra1-RPA was able to detect 1 × 10(1) copies of commercially synthesised Dra1 DNA as well as one S. haematobium egg within laboratory-spiked ddH(2)O samples. When compared with urine-egg microscopy, the overall sensitivity and specificity of the RT-ShDra1-RPA assay was 93.7% (±88.7–96.9) and 100% (±69.1–100), respectively. Positive and negative predictive values were 100% (±97.5–100) and 50% (±27.2–72.8), respectively. The RT-ShDra1-RPA therefore shows promise as a rapid and highly sensitive diagnostic tool able to diagnose urogenital schistosomiasis at the point-of-care.